(untitled) (Revista de Estudos da Linguagem, 2007)
This study set up to investigate the validity of different oral tasks,namely topic-based and picture-based narratives, as data elicitationtasks. Our ultimate goal was to examine whether these two types ofnarratives would impact upon intermediate learners’ L2 oralproduction, regarding their use of communication strategies (CS)during speech performance. Spearman correlational tests were runso as to check for ranking and frequency of the strategies used byparticipants in each narrative task. Results indicate that the type oftask and its intrinsic characteristics may affect the use of CS interms of frequency. Additionally, results show that the participantstended to experience fewer difficulties when performing the picturebasednarrative, which led them to use a fewer number of strategies.On the contrary, the two topic-based narratives led participants toapply a greater number of CS.